Distinguishing friends from foes: Can smRNAs modulate plant interactions with beneficial and pathogenic organisms?. (October 2022) - Pradhan, Maitree; Requena, Natalia
Abstract: In their agro-ecological habitats, plants are constantly challenged by fungal interactions that might be pathogenic or beneficial in nature, and thus, plants need to exhibit appropriate responses to discriminate between them. Such interactions involve sophisticated molecular mechanism of signal exchange, signal transduction and regulation of gene expression. Small RNAs (smRNAs), including the microRNAs (miRNAs), form an essential layer of regulation in plant developmental processes as well as in plant adaptation to environmental stresses, being key for the outcome during plant–microbial interactions. Further, smRNAs are mobile signals that can go across kingdoms from one interacting partner to the other and hence can be used as communication as well as regulatory tools not only by the host plant but also by the colonising fungus. Here, largely with a focus on plant–fungal interactions and miRNAs, we will discuss the role of smRNAs, and how they might help plants to discriminate between friends and foes.